The early years of the primary dealer system - Kenneth D. Garbade (Federal Reserve Bank of New York, 2016)
This paper presents a history of the primary dealer system from the late 1930s to the early 1950s. The paper focuses on two formal programs: the "recognized" dealer program adopted by the Federal Reserve Bank of New York in 1939 and the "qualified" dealer program adopted by the Federal Open Market Committee (FOMC) in 1944 and abandoned in 1953. Following his selection as Manager of the System Open Market Account (SOMA) in 1939, Robert Rouse formalized the New York Fed's system of "recognized" dealer counterparties. Although the Bank typically dealt with recognized dealers, it also did business from time to time with other dealers; neither the original informal system nor the successor formal system made a sharp distinction between the two. The focus of monetary policy changed from managing reserves to keeping interest rates low following the entry of the United States into World War II. To support the new focus, the FOMC replaced the New York Fed's recognized dealer program with its own program of "qualified" dealers. The new format limited transactions for the SOMA to qualified dealers and imposed a variety of restrictions on those dealers. Following the Treasury-Federal Reserve Accord of March 1951, the FOMC returned stewardship of the primary dealer system to the New York Fed, with instructions to develop a more open system that contemplated transactions with anyone "actually engaged in the business of dealing in Government securities."
Keywords: E5; G2; N1; 330; primary dealer; open market operations; System Open Market Account